Population estimates, consequences, and risk factors of obesity among pregnant and postpartum women in India: Results from a national survey and policy recommendations. (7th September 2020) - Chopra, Mansi; Kaur, Naman; Singh, Konsam Dinachandra; Maria Jacob, Chandni; Divakar, Hema; Babu, Giridhara R.; Hong Nguyen, Phuong; Bhanot, Arti; Sabharwal, Manisha; Deb, Sila; Baswal, Dinesh; Louise Killeen, Sarah; et al.
Abstract: Objective: To examine prevalence, risk factors, and consequences of maternal obesity; and provide evidence on current policies and programs to manage maternal obesity in India. Methods: This is a mixed‐methods study. We analyzed the National Family Health Survey (NFHS)‐4 data (2015–16) to estimate the prevalence and risk factors of obesity, followed by a desk review of literature and stakeholder mapping with interviews to develop policy guidance. Results: National prevalence of obesity (defined by WHO as body mass index ≥25) was comparable among pregnant (12%) and postpartum women (13%) ≥20 years of age. A high prevalence of obesity (>40%) was observed in over 30 districts in multiple states. Older maternal age, urban residence, increasing wealth quintile, and secondary education were associated with increased odds of obesity among pregnant and postpartum women; higher education increased odds among postpartum women only (OR 1.90; 95% CI, 1.44–2.52). Dietary variables were not associated with obesity. Several implementation challenges across healthcare system blocks were observed at policy level. Conclusion: Overall prevalence of obesity in India during and after pregnancy is high, with huge variation across districts. Policy and programs must be state‐specific focusing on prevention, screening, and management of obesity among pregnant and postpartum women. Abstract : Prevalence of maternal obesity in India is high with huge variations across districts, indicating the need for implementation of state‐specific policies to prevent, screen, and manage obesity as part of routine antenatal and postnatal care programs.